Resistance mechanisms to inhibitors of p53-MDM2 interactions in cancer therapy: can we overcome them - Haronikova, Lucia; Bonczek, Ondřej; Zatloukalova, Pavlina; Kokas-Zavadil, Filip; Kucerikova, Martina; Coates, Philip J; Fahraeus, Robin; Vojtesek, Borivoj (Cellular and Molecular Biology Letters, 2021)
Since the discovery of the first MDM2 inhibitors, we have gained deeper insights into the cellular roles of MDM2 and p53. In this review, we focus on MDM2 inhibitors that bind to the p53-binding domain of MDM2 and aim to disrupt the binding of MDM2 to p53. We describe the basic mechanism of action of these MDM2 inhibitors, such as nutlin-3a, summarise the determinants of sensitivity to MDM2 inhibition from p53-dependent and p53-independent points of view and discuss the problems with innate and acquired resistance to MDM2 inhibition. Despite progress in MDM2 inhibitor design and ongoing clinical trials, their broad use in cancer treatment is not fulfilling expectations in heterogenous human cancers. We assess the MDM2 inhibitor types in clinical trials and provide an overview of possible sources of resistance to MDM2 inhibition, underlining the need for patient stratification based on these aspects to gain better clinical responses, including the use of combination therapies for personalised medicine.
Keywords: Molecular Targeted Therapy; Drug Resistance, Bacterial; protoonkogenní proteiny c-mdm2; cílená molekulární terapie; Proto-Oncogene Proteins c-mdm2; nádory; klinické zkoušky jako téma; lidé; protinádorové látky; Neoplasms; nádorový supresorový protein p53; Humans; bakteriální léková rezistence; Tumor Suppressor Protein p53; Antineoplastic Agents; Clinical Trials as Topic